Bushiness in micropropagated Zantedeschia : an investigation at the environmental, physiological and molecular levels : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Plant Biology at Massey University, Palmerston North - D'Arth, Suzanne Maree (Massey University, 2003)
The commercial Zantedeschia industry faced a potentially serious problem with the cultivar Florex Gold periodically producing 'bushy' plants with several short non-flowering shoots and squat tubers with multiple nodes. These plants, derived from tissue culture, resulted in a reduced financial return to the Zantedeschia industry. A number of potentially causative factors were investigated in this project but no single factor emerged as the cause of the bushy syndrome. The selection of tubers with multiple eyes for initiation into tissue culture, or tubers themselves recently derived from tissue culture, may be a contributing factor to bushiness. A variable growing environment (screen house), shortened storage time (11 weeks) and plant position Were also shown to accentuate individual bushy characteristics. Endogenous cytokinin concentration and profile, determined by high performance liquid chromatography and radioimmunoassay, in tubers at three stages in the Zantedeschia life cycle were similar between bushy and non-bushy plants and cannot explain the bushy phenotype. Micropropagation of Florex Gold on Murashige and Skoog medium supplemented with low cytokinin concentration (4.4 µM 6-benzylaminopurine, 6-BAP) did not produce bushy plants or tubers. The use of elevated cytokinin during micropropagation did not produce plants with a range of bushy symptoms, although elevated thidiazuron (13.6 µM), but not 6-BAP, was shown to affect flower spathe length and plant shoot number. Florex Gold, when compared to a range of non-bushy Zantedeschia cultivars, displayed greater sensitivity to cytokinin during micropropagation assessed by a root length bioassay. Increased sensitivity to 6-BAP, during micropropagation may indicate a predisposition to bushiness. Differences in the DNA methylation profile of bushy and non-bushy plants were found in DNA using DNA Amplified Fragment Length Polymorphism. However, the isolated sequences were not similar to any gene(s) currently listed in public databases. Differential gene expression levels, determined by cDNA Amplified Fragment Length Polymorphism, found 60S and 18S ribosomal RNA down-regulated in bushy Florex Gold. These two genes may play a role in the expression of the bushy phenotype. Changes in DNA methylation and differential gene expression patterns and the results from the micropropagation experiments, provide evidence that Zantedeschia Florex Gold tubers selected for commercial micropropagation should be deep and apically dominant with few nodes and buds, and not themselves recently derived from tissue culture.
Keywords: Calla; Growth; Flowering; Plant micropropagation; Fields of Research::270000 Biological Sciences::270400 Botany::270402 Plant physiology